PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TGT TERHADAP HASIL BELAJAR MATEMATIKA MATERI PERKALIAN BERSUSUN - Rahma, Aulia Faiza; Sari, Elok Fariha (Faculty of Educational Sciences,Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2025)
This study aims to evaluate the effectiveness of the cooperative learning model Teams Games Tournament (TGT) in improving mathematics learning outcomes among fourth-grade students at SDN Jatisari, specifically on the topic of multi-digit multiplication. The research employed a quantitative approach using a pretest-posttest nonequivalent control group experimental design. The study involved two classes: an experimental group using the TGT model and a control group applying the Problem-Based Learning (PBL) model.The results indicate that the TGT model significantly enhanced students’ learning outcomes. The average posttest score of the experimental group was 85.32, higher than the control group’s average of 82.04. An independent sample t-test showed a significant difference between the two groups (Sig. 0.044 < 0.05), and a one-sample t-test revealed that the experimental group’s average posttest score exceeded the Minimum Mastery Criterion (KKM) of 75 (Sig. 0.000). The average learning gain (N-Gain) in the experimental group reached 55.94% (moderate category), which was higher than the control group’s 33.82%.The TGT model effectively fosters active student participation, collaborative learning, and a fun yet competitive classroom atmosphere. Therefore, the TGT model is recommended as an alternative instructional strategy to enhance mathematics learning outcomes at the elementary school level.